The Usefulness of Trabecular CT Attenuation Measurement at L4 Level to Predict Screw Loosening After Degenerative Lumbar Fusion Surgery: Consider Number of Fused Levels and Postoperative Sagittal Balance. Issue 10 (15th May 2022) - Shin, Hee Kwon; Koo, Hae-Won; Kim, Kwang Hyeon; Yoon, Sang Won; Sohn, Moon-Jun; Lee, Byung-Jou
Abstract : L4 t-ROI CT attenuation, number of fused levels, and postoperative sagittal balance were associated with screw loosening in lumbar fusion surgery. L4 t-ROI CT attenuation considering number of fused levels and postoperative sagittal balance is an accurate measurement method for predicting screw loosening. Abstract : Study Design: Retrospective study. Objective: To evaluate the absolute value of L4 trabecular region-of-interest (t-ROI) computed tomography (CT) attenuation, which can predict pedicle screw loosening, and determine the changes in value according to number of fused levels and sagittal balance in patients undergoing lumbar fusion surgery. Summary of Background Data: Although osteoporosis was not diagnosed in spinal dual x-ray absorptiometry preoperatively, we encountered several cases of screw loosening within 1 year of lumbar fusion surgery. Methods: We enrolled 478 patients and analyzed factors related to screw loosening. We evaluated the association between L4 t-ROI CT attenuation and screw loosening and determined the best cutoff value of t L4 t-ROI CT attenuation for predicting screw loosening. Results: The number of fused levels, postoperative C7-S1 sagittal vertical axis (SVA), and L4 t-ROI CT attenuation were independently correlated with screw loosening. According to number of fused level and postoperative C7-T1 SVA (≥36.9 mm or <36.9 mm), in patients with one-level fusion and C7-S1 SVA less than 36.9 mm, the optimal cutoff point of the L4 t-ROI CT attenuation predicting screw loosening was 106.5 Hounsfield unit (HU). L4 t-ROI attenuation did not change until two-level fusions. In patients with three-level fusions and C7-S1 SVA less than 36.9 mm, the optimal cutoff point of the L4 t-ROI CT attenuation predicting screw loosening was 159.0 HU. The optimal cutoff point of L4 t-ROI CT attenuation in patients with three-level fusions and C7-S1 SVA more than or equal to 36.9 mm was 191.0 HU. Conclusion: L4 t-ROI CT attenuation value considering number of fused levels and sagittal balance is an accurate measurement method to predict screw loosening. Spine surgeons should be aware of the L4 t-ROI attenuation before surgery to improve the fusion rate and reduce instrument-related complications of lumbar spine surgery in osteoporotic patients. Level of Evidence: 3